UPAYA PROTEKSI TERHADAP KONTAMINASI NEGATIF MASYARAKAT DI KAMPUNG CIKOLE: UPAYA PROTEKSI TERHADAP KONTAMINASI NEGATIF MASYARAKAT DI KAMPUNG CIKOLE - Abdul Mun'im Amaly; Septy Ayu; Jamaludin Jamaludin (LPPM STAI Darul Falah, 2023)
Education is the main gate to the progress and manners of a nation. If you don't get an education, it will raise problems in society, one of which is in Kampung Cikole, moral degradation, and distortion of the educational paradigm. The purpose of community service is to help provide solutions and real efforts to solve problems happened, by involving students, leaders, and the community of Cikole village, researchers took a holistic approach to be able to identify what needs to be done so that the problems that occurred in Cikole village could be resolved properly. Based on the research conducted after the researchers implemented the smart home program, recitation, and regular congregation as well as educational outreach, the people of Cikole village began to form Islamic characters and understand the importance of education, and responded well to the positive changes that researchers implemented in Cikole village.